ПАРЛАМЕНТЫН ГИШҮҮДИЙН ТООГ ЗОХИСТОЙ ТОГТООХ АСУУДАЛД - Д.Сүхболд (Politology, 2024)
This article describes some methods for determining the appropriate number of members of parliament that reflect the will of the majority of the people and is written with the aim of conducting a theoretical, methodological and mathematical analysis of the reasons for the increase in the number of members of the State Great Hural to 126 as a result of an amendment to the Constitution of Mongolia in 2023. In particular, this article can be innovative and significant because it studies the basics of the cube root method, which is the basis for increasing the number of deputies of the State Great Hural , compares its positive and negative aspects, and also makes theoretical-methodological and mathematical analyzes.